A unified model of cusp spot, High Latitude Dayside aurora (HiLDA)/(Space Hurricane), and 15MLT-PCA - DeSheng Han; YaTing Xiong; Run Shi; HuiXuan Qiu; HuiTing Feng (Earth and Planetary Physics, 2023)
Cusp spot, High Latitude Dayside aurora (HiLDA), ‘space hurricane’, and 15MLT-PCA (Polar Cap Arc observed around 15:00 Magnetic Local Time) are mesoscale auroral structures observed in the polar cap region. They share many common properties and, at the same time, have notable differences. A 15MLT-PCA is a polar cap arc connected to the auroral oval, but the others are auroral spots detached from the oval. A cusp spot differs from a HiLDA in local time location. A space hurricane differs from a HiLDA in having spiral-arm structures. Until now, relationships among these auroras have not been depicted clearly. Here we propose a unified model, based on lobe reconnection, that encompasses their similarities and differences. We then provide critical supporting evidence for the model. The model suggests that different reconnection sites under different IMF conditions result in these differently-appearing auroral forms. The model explains all the characteristic features of these auroras and has implications for understanding the dawn/dusk and inter-hemispheric asymmetries observed in their occurrence patterns. We anticipate confirmation of the model by observations to be made during the Solar wind-Magnetosphere-Ionosphere Link Explorer (SMILE) mission. Moreover, since the model indicates that these auroras appear on the footprint of the poleward cusp boundary, we expect data from the SMILE mission to make it possible to estimate the approximate shape of the cusp.